Effects of chronic job insecurity on Big Five personality change - Wu, Chia-Huei; Wang, Ying; Parker, Sharon; Griffin, Mark (American Psychological Association, 2020)
Drawing on Cybernetic Big Five Theory, we propose that chronic job insecurity is associated with an increase in neuroticism and decreases in agreeableness and conscientiousness (the 3 traits that reflect stability). Data collected from 1,046 employees participating in the Household, Income and Labor Dynamics in Australia survey over a 9-year period were analyzed. Job insecurity and the other job-related variables (i.e., job control, time demand, and job stress) were measured in all years, and personality was measured at the first, fifth, and ninth years. We applied latent trait-state-occasion modeling and specified models using variables across two timeframes (from Time 1 to Time 4 and from Time 5 to Time 9). Results showed that chronic job insecurity over four or five preceding years predicted a small increase in neuroticism and a small decrease in agreeableness in both timeframes, and a small decrease in conscientiousness in the first timeframe. We also found that chronic job stress explained the association between chronic job insecurity and the increase in neuroticism, but not changes in other personality traits, in the first timeframe. Similar results were obtained when the entire 9-year timeframe was examined. The results generally showed null effects of chronic job insecurity with regard to extraversion and openness (the traits that reflect plasticity). This study suggests that job insecurity has important implications for one's personality when experienced over a long-term period.